Development of a Chemo-Entrepreneurship–Based Chemistry Practicum E-Module - Hayatuz Zakiyah (MANDAILING GLOBAL EDUKASIA, 2025)
Various instructional methods can be implemented by educators to encourage students to think critically, creatively, and innovatively. One approach that can be applied in the learning process is the use of learning resources that are capable of enhancing students’ skills and creativity, such as practicum e-modules. The development of a Chemo-Entrepreneurship–based practicum e-module in chemistry learning was motivated by the absence of practicum guides currently used in schools that incorporate Chemo-Entrepreneurship principles. Through the Chemo-Entrepreneurship (CEP) approach embedded in the practicum module, the chemistry content learned by students can be applied in laboratory activities to process materials into useful chemical products with economic value. This approach is expected to foster students’ entrepreneurial interest and inspiration through the learning process. This initiative is also aligned with the implementation of the Merdeka Curriculum, which emphasizes meaningful, contextual, and student-centered learning. The research problems addressed in this study are: (1) the validity of the developed Chemo-Entrepreneurship–based chemistry practicum e-module, and (2) the responses of teachers and students toward the developed Chemo-Entrepreneurship–based chemistry practicum e-module. This study employed a Research and Development (R&D) method using the 4D model, which consists of four stages: define, design, develop, and disseminate. The research sample consisted of 33 students from class XII MIA 1 at MAN 4. The data collection instruments included interview guidelines for the initial analysis stage, validation sheets, and questionnaire sheets for teachers and students. Data analysis techniques were carried out using percentage formulas. Based on the validation results from three expert validators, the e-module obtained a percentage score of 81.4%, which falls into the “very valid” category. Furthermore, questionnaire responses from two chemistry teachers yielded a percentage of 92.3%, categorized as “very good,” while responses from 33 students of class XII MIA 1 resulted in a percentage of 75.8%, categorized as “good”.